The Flash. The complete fourth season [videorecording (DVD)] - Berlanti, Greg; Kreisberg, Andrew, 1971-; Johns, Geoff, 1973- (Warner Bros. Entertainment, 2018)
Last season, Barry Allen, aka the Flash, used his extraordinary abilities to travel back in time and save his mother's life, and inadvertently created an alternate timeline known as Flashpoint. The phenomenon not only gave birth to the villainous God of Speed known as Savitar, but changed the lives of Caitlin Snow and Wally West forever. With the help of his adoptive father, Detective Joe West, his fiancée Iris West, and the others, Barry continues to protect the people of Central City.